Dermal fillers in aesthetics: an overview of adverse events and treatment approaches - Funt D; Pavicic T (Dove Medical Press, 2013)
David Funt,1 Tatjana Pavicic21Mount Sinai Hospital, Department of Plastic Surgery, New York, NY, USA; 2Department of Dermatology and Allergy, Ludwig-Maximilian University of Munich, Munich, GermanyBackground: The ever-expanding range of dermal filler products for aesthetic soft tissue augmentation is of benefit for patients and physicians, but as indications and the number of procedures performed increase, the number of complications will likely also increase.Objective: To describe potential adverse events associated with dermal fillers and to provide structured and clear guidance on their treatment and avoidance.Methods: Reports of dermal filler complications in the medical literature were reviewed and, based on the publications retrieved and the authors' extensive experience, recommendations for avoiding and managing complications are provided.Results: Different dermal fillers have widely varying properties, associated risks, and injection requirements. All dermal fillers have the potential to cause complications. Most are related to volume and technique, though some are associated with the material itself. The majority of adverse reactions are mild and transient, such as bruising and trauma-related edema. Serious adverse events are rare, and most are avoidable with proper planning and technique.Conclusion: For optimum outcomes, aesthetic physicians should have a detailed understanding of facial anatomy; the individual characteristics of available fillers; their indications, contraindications, benefits, and drawbacks; and ways to prevent and avoid potential complications.Keywords: aesthetic medicine, complications